IMPLEMENTASI METODE PEMBERIAN TUGAS DALAM MENINGKATKAN KEMAMPUAN GURU MEMBUAT MEDIA PEMBELAJARAN DI SLB SRI MUJINAB PEKANBARU - Yasni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article is focused on the teachers’ low competency to make learning media at Sri Mujinab Special School Pekanbaru. It is derived from 1) the lack of teachers’ competency to make learning media, 2) learning tools that are only used as a compliment and not for teaching needs, 3) a number of teachers who asked about the learning tools they answer have or have not to make them yet, and 4) teachers who rarely used media learning, in fact, at the low-grade level, students really needed media as learning aids. Above all, the author could formulate the problem that was based on the teacher's competency to make learning media and could be improved through the assignment method at Sri Mujinab SLB Pekanbaru. The research used School Action Research designed by Kurt Lewin. The main concept of PTS proposed by Kurt Lewin consisted of four components, planning, action, observation, and reflection. Based on the description of data process and discussion, it was found that the teacher's competency to make learning media was obtained in the first cycle with a percentage of 65% in the good category and in the second cycle was obtained the improvement percentage of 88% in the very good category.